2001
DOI: 10.1051/0004-6361:20011102
|View full text |Cite
|
Sign up to set email alerts
|

Far-infrared mapping of the starburst galaxy NGC 253 with ISOPHOT

Abstract: Abstract.A 180 µm map and strip maps at 120 and 180 µm were obtained for the edge-on starburst galaxy NGC 253 with ISOPHOT, the photometer on board the Infrared Space Observatory. We compare these observations with those obtained by IRAS at 60 µm and 100 µm and derive the far-infrared spectral energy distribution at different locations in the galaxy. There is evidence for the presence of cold dust (T ≤ 20 K) both in the nucleus and in the disk. Extended emission dominated by cold dust is detected up to ∼15 (∼1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 30 publications
6
65
0
Order By: Relevance
“…The dust temperature in the calculation above is from the peak brightness temperature of the 12 CO lines at the continuum sources. It is also consistent, within a factor of two, with the dust temperatures inferred for the nuclear region by fitting the spectral energy distribution (SED) in the far-infrared (Radovich et al 2001;Melo et al 2002;Weiß et al 2008). We did not subtract non-dust emission from the continuum or correct the continuum flux density for missing flux because the two corrections are less than a few 10% each and are in opposite directions.…”
Section: Mass and Column Density From Continuumsupporting
confidence: 80%
See 1 more Smart Citation
“…The dust temperature in the calculation above is from the peak brightness temperature of the 12 CO lines at the continuum sources. It is also consistent, within a factor of two, with the dust temperatures inferred for the nuclear region by fitting the spectral energy distribution (SED) in the far-infrared (Radovich et al 2001;Melo et al 2002;Weiß et al 2008). We did not subtract non-dust emission from the continuum or correct the continuum flux density for missing flux because the two corrections are less than a few 10% each and are in opposite directions.…”
Section: Mass and Column Density From Continuumsupporting
confidence: 80%
“…The warmer gas in NGC 253 is consistent with the larger luminosity of the starburst nucleus and in accordance with the higher dust temperature there. The dust temperature in the Galactic CMZ has been estimated to be ∼20 K from SED fitting in the submillimeter-to-far-infrared bands (Pierce-Price et al 2000, and references therein), while dust in the center of NGC 253 was estimated also from SED fitting to be at or above 30 K (Radovich et al 2001;Melo et al 2002;Weiß et al 2008). The high-temperature gas in the center of NGC 253 has also been pointed out from the line excitation analyses mentioned in Section 3.4.…”
Section: Comparison With the Center Of Our Galaxymentioning
confidence: 99%
“…Our estimate of the intrinsic ER luminosity is somewhat lower than that derived by Soifer et al (2002) and Spoon et al (2004), who found a lower limit of $7 ; 10 10 L , but confirms qualitatively their results. The starburst luminosity in the ER seems to be similar to that of moderately bright infrared galaxies, such as NGC 253 (Radovich et al 2001).…”
Section: II and O Imentioning
confidence: 77%
“…These temperature measurements have shown that the dust is warmer in the centers of galaxies than in the outskirts (e.g., Alton et al 1998;Radovich et al 2001;Melo et al 2002;Dupac et al 2003). Cool dust at roughly the same temperature in spiral disks is detected globally at longer wavelengths (850 μm and 1.3 mm; Siebenmorgen et al 1999;Dunne et al 2000Dunne et al , 2001Vlahakis et al 2005), but there is also some evidence of a Herschel is an ESA space observatory with science instruments provided by the European-led Principal Investigator consortia and with important participation from NASA.…”
Section: Introductionmentioning
confidence: 99%